Unveiling the Cultural and Historical Significance: Implications of Linguistic Anthroponymy from Chess Openings - Pratama, Luthfi Hakim Bintang; Kepirianto, Catur (Publikasi Indonesia, 2025)
This study explores the intriguing connections between anthroponymy and chess, revealing how the names of chess openings offer captivating insights into the game’s history and culture. Drawing inspiration from the popularity of chess streamers on YouTube, the research adopts a qualitative content analysis approach to examine the linguistic and cultural origins of commonly used chess openings. Data are sourced from James Eade’s “Chess Openings for Dummies” (2021). The findings showcase that numerous opening names are rooted in geography, such as the “Sicilian Defense” and “French Defense”, while others are named after notable individuals, such as the “Philidor Defense” and “Evans Gambit”. In addition, some openings commemorate famous games or events, like the “Muzio Gambit” and “Englund Gambit”. This pioneering study enriches the fields of chess and language studies, as well as education and anthroponymy, by providing a fresh perspective on the evolution of chess and its linguistic connections. Future research avenues may explore additional openings and further investigate the cultural, regional, and historical influences behind the nomenclature of chess openings. Furthermore, this research suggests the integration of anthroponymy and chess into interdisciplinary education, fostering a deeper understanding of geography, history, English, and cultural references through the study of chess openings